Virilizing Lipid Cell Tumor of the Ovary: Light and Electron Microscopic Studies - Lim, Sook K. (1983)
Lipid cell tumor of the ovary is among the rarest tumors belonging to the virilizing group of ovarian neoplasms. A lipid cell tumor of the ovary is described in an 18-year-old woman with secondary amenorrhea, hirsutism, and frank virilization. Current diagnostic features, preoperative and postoperative androgen determinations, and histomorphological and ultrastructural studies are presented. Prompt diagnosis and treatment are emphasized in this potentially malignant and disfiguring androgenic tumor that is readily amenable to surgery.